Analytical design of fractional order PID controllers based on the fractional set-point weighted structure: Case study in twin rotor helicopter. (October 2015) - Azarmi, Roohallah; Tavakoli-Kakhki, Mahsan; Sedigh, Ali Khaki; Fatehi, Alireza
Highlights: Presenting a new analytical method for designing set-point weighted fractional order PID controller. Presenting a simple analytical method for designing filtered fractional order PI controller. Verifying the theoretical results on a laboratory scale twin rotor helicopter experimentally. Abstract: In this paper, an analytical method for tuning the parameters of the set-point weighted fractional order PID (SWFOPID) controller is proposed. The studied control scheme is the filtered fractional set-point weighted (FFSW) structure. Also to achieve a desired closed-loop performance, a fractional order pre-filter is employed. The proposed method is applicable to stable plants describable by a simple three-parameter fractional order model. Such a model can be considered as the fractional order counterpart of a first order transfer function without time delay. Finally, the proposed method is implemented on a laboratory scale CE 150 helicopter platform and the results are compared with those of applying a filtered fractional order PI (FFOPI) controller in a similar structure. The practical results show the effectiveness of the proposed method.